Understanding the Effect of Large Wildfires on Residents' Well-Being: What Factors Influence Wildfire Impact?. Issue 1 (22nd October 2015) - Paveglio, Travis B.; Kooistra, Chad; Hall, Troy; Pickering, Michael
Abstract : Existing social science has indicated that wildfires can affect the short- and long-term functioning of social systems. Less work has focused on how wildfire events affect the physical and psychological well-being of individual residents impacted by such events. In this study, we explore the extent to which personal- or community-level impacts, biophysical characteristics of a wildfire, and resident expectations about wildfire influence residents' self-reported well-being following such events. In fall 2013, we surveyed residents who were potentially impacted by 25 wildfires in Washington, Oregon, Idaho, and Montana. Multivariate regression was used to determine the influences on wildfire impact to resident well-being, and hierarchical linear modeling (HLM) was used to test for variance in impacts to resident well-being across the 25 fires selected. The results suggest that a loss of connection to the landscape postfire, personal impacts such as damage to property, residents' expectations about wildfire impact in their locality, and disruption of resident routines were highly correlated with self-reported well-being after fires. Results of the HLM analysis suggest a high level of consistency in the relationships that influenced well-being across the 25 fires. Our findings indicate that common metrics could be used to help establish baselines for measuring impacts to well-being from fires.